The correlation between pre-treatment symptoms, acute and late toxicity and patient-reported health-related quality of life in non-small cell lung cancer patients: Results of the REQUITE study. (November 2022) - van der Weijst, Lotte; Azria, David; Berkovic, Patrick; Boisselier, Pierre; Briers, Erik; Bultijnck, Renée; Chang-Claude, Jenny; Choudhury, Ananya; Defraene, Gilles; Demontois, Sylvian; Elliott, Rebecca M.; Ennis, Dawn; et al.
Highlights: Pre-treatment symptoms impact HRQoL and its functional domains in NSCLC. After radiotherapy, overall and specific toxicities impact HRQoL and its domains. Dyspnoea as symptom and toxicity is crucial in this association with HRQoL. Toxicity after concurrent chemo-radiotherapy and 3D-CRT most negatively affects HRQoL. It is important to limit radiation-induced toxicity to ensure HRQoL in NSCLC. Abstract: Background and purpose: To investigate the association between clinician-scored toxicities and patient-reported health-related quality of life (HRQoL), in early-stage (ES-) and locally-advanced (LA-) non-small cell lung cancer (NSCLC) patients receiving loco-regional radiotherapy, included in the international real-world REQUITE study. Materials and methods: Clinicians scored eleven radiotherapy-related toxicities (and baseline symptoms) with the Common Terminology Criteria for Adverse Events version 4. HRQoL was assessed with the European Organization for Research and Treatment of Cancer core HRQoL questionnaire (EORTC-QLQ-C30). Statistical analyses used the mixed-model method; statistical significance was set at p = 0.01. Analyses were performed for baseline and subsequent time points up to 2 years after radiotherapy and per treatment modality, radiotherapy technique and disease stage. Results: Data of 435 patients were analysed. Pre-treatment, overall symptoms, dyspnea, chest wall pain, dysphagia and cough impacted overall HRQoL and specific domains. At subsequent time points, cough and dysphagia were overtaken by pericarditis in affecting HRQoL. Toxicities during concurrent chemo-radiotherapy and 3-dimensional radiotherapy had the most impact on HRQoL. Conversely, toxicities in sequential chemo-radiotherapy and SBRT had limited impact on patients' HRQoL. Stage impacts the correlations: LA-NSCLC patients are more adversely affected by toxicity than ES-NSCLC patients, mimicking the results of radiotherapy technique and treatment modality. Conclusion: Pre-treatment symptoms and acute/late toxicities variously impact HRQoL of ES- and LA-NSCLC patients undergoing different treatment approaches and radiotherapy techniques. Throughout the disease, dyspnea seems crucial in this association, highlighting the additional effect of co-existing comorbidities. Our data call for optimized radiotherapy limiting toxicities that may affect patients' HRQoL.